Implications of Social Interaction in Pandemic Period for the Millennial Generation - Aulia Bethari Prasiwi; Riska Yuni Pramudita; Putri Almaidah; Moses Glorino Rumambo Pandin (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
We created the context of this research by looking at the many problems that exist that the Covid 19 virus has a huge impact on social interaction. Therefore, our team conducted research on changing social interactions in society with the aim of knowing that changes in social interactions that occurred during this pandemic would have a good or bad impact. Later in this study, there will be several questions regarding the views of a student about social interaction in Indonesia during the Covid 19 pandemic. The questions contain (1) Will interacting through virtual media be more effective than direct interaction? (2) Has social interaction during the pandemic changed in a negative direction?, and there are several questions that contain the negative and positive impacts of changes in social interaction during the pandemic. Later this research will use a quantitative approach method by collecting some data through a questionnaire on the google form that has been created. After that, the result will be that social interaction during a pandemic like now has changed in a positive direction. We recommend research to the general public and students. The limitation in this study is that our team only used responses via questionnaires from students of the Faculty of Economics and Business, Airlangga University batch 2021.